Peralihan Benda Bergerak Aset Harta Bersama Tanpa Persetujuan Salah Satu Pihak - Isadora Nathania Edgar; Siti Mahmudah (Notaire, 2023)
AbstractUnlike immovable thing, movable thing can move or be moved more easily. The transfers of movable things are often done with a short and practical process so that the origin of the object is not explored in detail first. This opens a loophole for violations of the authority to act on marital community of property assets in the form of movable things. This research aims to clearly know the authority to act on marital community of property assets and also how about the legal protection in case there is a transfer of movable thing of marital community of property assets without the consent of one of the parties. The research method used in this study is normative-juridical. Based on the results of this research, it is known that eiher the husband or wife individually doesn’t have the authority to make transfer movable thing of marital community of property without the consent of their spouse who is the owner of it too. The legal act of transferring registered movable thing of marital community of property assets that is carried out by the approval of their spouse means violating the authority to act that has been determined by the law which caused the legal action is being invalid and void, while for unregistered movable thing applied Article 1977 of Indonesian Civil Code and there’s protection for receipient of that movable thing in good faith which causes the legal action to remain valid and the aggrieved party can claim compensation from their spouse.Keywords: Marital Community Of Property; Authority To Act; Violation. AbstrakBerbeda dengan benda tak bergerak, benda bergerak bersifat dapat berpindah atau dipindahkan dengan lebih mudah. Peralihan benda bergerak acapkali dilakukan dengan proses singkat dan praktis sehingga asal – usul benda tersebut tidak ditelusuri secara rinci terlebih dahulu. Hal ini membuka celah bagi terjadinya pelanggaran atas kewenangan bertindak terhadap aset harta bersama yang berupa benda bergerak. Penelitian ini bertujuan untuk mengetahui secara jelas kewenangan bertindak atas aset harta bersama dan juga bagaimana perlindungan hukum dalam hal terjadi peralihan benda bergerak aset harta bersama tanpa persetujuan salah satu pihak. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif. Berdasarkan hasil penelitian diketahui bahwa suami atau istri secara masing – masing tidak memiliki wewenang untuk melakukan perbuatan pengalihan hak atas benda bergerak aset harta bersama tanpa persetujuan kawan kawinnya yang merupakan pemilik juga atas aset harta bersama tersebut. Perbuatan hukum pengalihan aset harta bersama berupa benda bergerak terdaftar yang dilakukan tanpa persetujuan salah satu pihak artinya melanggar wewenang bertindak yang telah ditentukan oleh undang – undang yang mengakibatkan perbuatan hukum tersebut tidak sah dan konsekuensinya adalah batal, sedangkan untuk benda bergerak tidak terdaftar berlaku pasal 1977 Kitab Undang – Undang Hukum Perdata serta terdapat perlindungan bagi penerima pengalihan benda tersebut dengan itikad baik yang mengakibatkan perbuatan hukumnya tetap sah dan pihak yang dirugikan dapat meminta ganti kerugian kepada pihak yang mengalihkan harta bersama tersebut.Kata Kunci: Pailit; Kepailitan Transnasional; Aset Debitur.